2003
DOI: 10.1097/01.smj.0000056659.05183.62
|View full text |Cite
|
Sign up to set email alerts
|

Practice Profiles, Procedures, and Personal Rewards According to the Sex of the Physician

Abstract: Practice patterns of male and female physicians were generally similar. However, significant differences were noted in geriatric care, procedures, and salary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…They also saw fewer older-aged patients than their male counterparts [1,23]. These results survived multivariate analyses that accounted for the age of physician, practice location, and graduation period [25].…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…They also saw fewer older-aged patients than their male counterparts [1,23]. These results survived multivariate analyses that accounted for the age of physician, practice location, and graduation period [25].…”
Section: Resultsmentioning
confidence: 93%
“…In countries where the difference in hours was statistically significant (12 of 32 study countries), male PCPs worked more in ten, and female PCPs worked more in two [18]. Results from North America are similar, with female PCPs working between four and 14.5 fewer patient-care hours per week [8,19-23]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings are consistent with those of others, showing a sex-based difference in procedural practice. 38,39 For example, Lewis et al 37,38 found that male primary care physicians were more than two times more likely (OR = 2.61) to report performing flexible sigmoidoscopy or wishing to train to perform it. The reasons for this type of sex discrepancy are not clear.…”
Section: Discussionmentioning
confidence: 99%